Analisis Persepsi Karyawan Pada Kemudahan Akses Pembiayaan Bank Syariah dan Lembaga Pembiayaan Informal di PT Kanindo Makmur Jaya 2 - Faridlotun Nimah; Wahidullah Wahidullah; Miswan Ansori (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the perceptions of PT Kanindo Makmur Jaya 2 employees regarding the ease of access to financing through Islamic banks and informal financing institutions. The research method used qualitative data collection techniques through interviews, observation, and documentation. The results showed that employees perceived Islamic banks as having complicated procedures, requiring numerous documents, and taking a long time to disburse funds, while informal financing institutions were considered more accessible, fast, and flexible despite having high interest risks. Convenience and speed were the main reasons employees chose informal institutions to meet urgent economic needs. This study concluded that low levels of Islamic financial literacy and minimal product socialization have led to negative perceptions of Islamic banks, so strategies to improve education and simplify procedures are needed to expand Islamic financial inclusion among factory workers.